Tawāzun as Religious Approach in Post-Mining Land Management - Syamsul Hadi Untung; Yuangga Kurnia Yahya; Linda Alfionita (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
This study aims to examine the environmental impact of mining activities from the Islamic perspective. The issue of concern in this article is the ex-mining pits that are not reclaimed nor being rehabilitated in post-mining activities. From the standpoint of al-tawāzun al-bī’ī, good mining practices mean returning land and water's function to their original position with improved quality to maintain a balance in environmental management and minimize the resulting damage, including those that cost people's lives. For this purpose, the religious approach and values play a central role in spreading good awareness among Indonesian people, known as a religious society.